THE EFFECT OF PICTIONARY GAME ON THE STUDENTS’ WRITING ABILITY AT THE TENTH GRADE OF MAS AL-HASYIMIYAH TEBING TINGGI - Rinanda, Kartika (BRIGHT VISION Journal of Language and Education, 2021)
The research was conducted to know the significant effect of Pictionary game of students’ writing ability which was observed from the students at the tenth grade of MAS Al-Hasyimiyah Tebing Tinggi. The research method of this paper was quantitative research by using quasi-experimental research. The population of the research was the tenth grade of MAS Al-Hasyimiyah Tebing Tinggi. In taking the sample, the researcher used saturated sampling which took all of the students in the tenth grade. The two classes divided into experimental class and control class. There were 25 students in experimental class and 25 students in control class. In experimental class, the researcher taught by using Pictionary game, meanwhile the control class that used conventional method. In experimental class that was taught by Pictionary game, the increase of the mean score was 21.4 and in control class was taught by conventional method, the increase of the mean score was 5.08. The calculation of T-test by using SPSS v.23 in post-test of both classes, the researcher found that the value of the Sig. score was 0.000. It means that the Sig. core was smaller than 0.005 (0.000 < 0.05). It can be concluded that there were significant differences between the two classes; experimental class and control class. It showed that Pictionary game gave the effect on students’ writing ability at the tenth grade of MAS Al-Hasyimiyah Tebing Tinggi.